Application of health self-management intervention program for metabolic syndrome patients in the bereaved population following the Wenchuan earthquake - Lihua, Ma; Xiaolian, Jiang; Song, Wang; Ning, Jiang (Frontiers in Public Health, 2023)
The destructive Wenchuan earthquake has led to approximately 800,000 people being bereaved. In the previous cross-sectional study, we exploredand studied its influencing factors among the bereaved population 12 years after the Wenchuan earthquake. Chronic disease self-management has become a recognized public health service. Due to the Wenchuan earthquake being a serious stress event, the implementation of targeted interventions should be discussed further. Objectives:To verify the effect of applying a self-management intervention program for patients with MS among the bereaved population following the Wenchuan earthquake. Design: A randomized controlled trial (RCT) design was adopted. Participants: A total of 132 bereaved patients with MS following the Wenchuan earthquake constituted the sample. Methods: The study was based on the Cognitive-Phenomenological-Transaction, Chronic Disease Self-Management Program, and Patient Empowerment ConceptualModel, which combined with the latest evidence-based guidelines, were used to systematically evaluate cross-sectional results of this study that were used to construct a stress management-based health self-management intervention program and MS health self-management manual for bereaved patients with MS following the Wenchuan earthquake. In addition, we revised and completed a health self-management intervention program and health self-management manual for patients with MS by using the expert consultation method. General data were collected prior to intervention (T0). We collected the patients' MS disease-related physiological indicators before intervention (T0), after intervention (T1), and 2 months after intervention (T2). EipData3.1 software was used to input data in duplex and duplicate, and SPSS22.0 software was used for statistical analysis.The variance analysis showed that the total score of healthy self-management behavior and the score of diet management, exercise management, drug management, and emotional management have intergroup effects, time effects, and grouptime interaction effects (P < 0.05). When the differences between groups were further compared, we found that the total score and the score of six dimensions (excluding disease self-monitoring management) were higher than those of the control groups at T1 and T2, and the differences were statistically significant (P < 0.05).The intervention program of healthy self-management for patients with MS who come from bereaved families following the Wenchuan earthquake can effectively improve patients' health self-management behaviors.